Soil microbial biomass after three-year consecutive composted tannery sludge amendment - Silva, M. D. M.; Barajas-Aceves, M.; Araujo, A. S. F.; Araujo, F. F.; Melo, W. J. [UNESP] (Science Press, 2014)
Brazilian industry produces huge amounts of tannery sludge as residues, which is often disposed by landfilling or land application. However, consecutive amendment of such composted industrial wastes may cause shifts in soil microbial biomass (SMB) and enzyme activity. This study aimed to evaluate SMB and enzyme activity after 3-year consecutive composted tannery sludge (CTS) amendment in tropical sandy soils. Different amounts of CTS (0.0, 2.5, 5.0, 10.0, and 20.0 t ha(-1)) were applied to a sandy soil. The C and N contents of SMB, basal and substrate-induced respiration, respiratory quotient (qCO(2)), and enzyme activities were determined in the soil samples collected after CTS amendment for 60 d at the third year. After 3 years, significant changes were found in soil microbial properties in response to different CTS amounts applied. The organic matter and Cr contents significantly increased with increasing CTS amounts. SMB and soil respiration peaked following amendment with 10.0 and 20.0 t ha(-1) of CTS, respectively, while qCO(2) was not significantly affected by CTS amendment. However, soil enzyme activity decreased significantly with increasing CTS amounts. Consecutive CTS amendment for 3 years showed inconsistent and contrasting effects on SMB and enzyme activities. The decrease in soil enzyme activities was proportional to a substantial increase in soil Cr concentration, with the latter exceeding the permitted concentrations by more than twofold. Thus, our results suggest that a maximum CTS quantity of 5.0 t ha(-1) can be applied annually to tropical sandy soil, without causing potential risks to SMB and enzyme activity.
Keywords: Cr concentration; enzyme activity; Industrial waste; soil microbial properties; Tropical soil